Safety and efficacy of SHR4640 combined with febuxostat for primary hyperuricemia: a multicenter, randomized, double-blind, phase II study. (January 2022) - Tang, Honghu; Cui, Beibei; Chen, Yiyu; Chen, Lin; Wang, Zhihong; Zhang, Ning; Yang, Yanlan; Wang, Xiaodong; Xie, Xiangliang; Sun, Lingyun; Dang, Wantai; Wang, Xianyang; et al.
Background: To evaluate the safety, tolerability, and efficacy of SHR4640, a highly selective urate transporter-1 inhibitor, in combination with febuxostat, in patients with primary hyperuricemia. Methods: In this randomized, double-blind, parallel-controlled phase II study, patients whose fasting serum uric acid (sUA) levels were ⩾ 480 μmol/L at screening with gout or sUA levels were ⩾ 420 μmol/L lasting for at least 3 months without gout, either with sUA levels ⩾ 540 μmol/L at screening or sUA levels ⩾ 480 μmol/L with comorbidities at screening, were enrolled. Patients were randomized (1:1:1) to receive SHR4640 10 mg plus febuxostat 80 mg, SHR4640 10 mg plus febuxostat 40 mg, and SHR4640 5 mg plus febuxostat 20 mg orally once daily. The primary end point was the incidence of treatment-emergent adverse events (TEAEs). Results: A total of 93 patients were randomized and received treatment. TEAEs occurred in 55.9% of patients. The incidence of TEAEs was comparable among all the groups. Serious TEAEs occurred in one patient (1.1%), with no deaths observed. The proportion of patients who achieved the target sUA levels by week 4 was 79.3%, 96.6%, and 75.0% in the SHR4640 10 mg plus febuxostat 80 mg, SHR4640 10 mg plus febuxostat 40 mg, and SHR4640 5 mg plus febuxostat 20 mg groups, respectively. The mean percent reduction of sUA was 59.7%, 63.7%, and 41.8%, respectively. Conclusion: SHR4640 plus febuxostat exhibited a tolerable safety profile and substantial sUA lowering activity in patients with primary hyperuricemia. Registration: www.chinadrugtrials.org.cn ; CTR 20192429